Procesamiento y desarrollo de productos de yuca - Wheatley, Christopher C.; Best, R. (International Center for Tropical Agriculture, 1991)
Since product development according to consumer-defined specifications constitutes a key to success for integrated cassava products, the process for generating and selecting concepts for new products and turning them into successful commodities are described. New products also cover traditional cassava products which are improved through better quality and/or more efficient processing. Similarities and differences are pointed out between product development for the commercial food industry and the development of cassava-based products through integrated cassava projects. Steps for defining the development of new cassava products are idea generation, idea screening, concept testing, feasibility study, product and process development and testing, market plan, test plan, commercial launch and expansion, and evaluation. Categories for evaluating new product market potential are marketability, life span of the product in the market place, productive ability, and growth potential. A strong research input is needed for product development in cassava, at all stages. Macroeconomic research is needed to screen ideas and for feasibility studies, while marketing research is obviously important in the areas of concept development and test marketing. Both types of research, in addition to technical research, are important in the product development and testing phase, where the process is refined at the pilot plant, real costs are obtained, and the product is available for consumer testing. (CIAT)